Analysis of the Dynamics of Cross-Sector Collaboration: Towards an Optimized Framework for MSMEs Development - Maryam, Maryam; Husniati, Ade Muana; Muryali, Muryali; Aiyub, Aiyub; Mwaijande, Francis (Universitas Teuku Umar, 2025)
The development of excellent MSMEs plays a crucial role in economic growth. However, in developing countries, MSME growth has stagnated due to weak stakeholder collaboration. Although previous studies have explored this issue, the understanding of stakeholder interactions holistically remains incomplete. Moreover, no concrete framework has been proposed to enhance collaboration. This research addresses these gaps by applying system thinking and a collective impact approach to develop an ideal collaboration framework. Using a qualitative case study method, informants were selected through purposive sampling, covering four key actors: the public sector, private sector, MSMEs, and the community. Findings indicate that MSME collaboration in Lhokseumawe remains fragmented, lacking synergy to achieve collective impact. The proposed framework defines four key roles: (1) the public sector should enhance training, capital access, regulations, and leadership; (2) the private sector should increase investment; (3) MSMEs must strengthen solidarity, ethics, adaptability, and entrepreneurial motivation; and (4) the community should foster security and stability. This integrated approach ensures a more effective collaboration model to drive MSME growth and sustainability.